2015
DOI: 10.1063/1.4930280
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of amyloid formation and the role of intersheet interactions

Abstract: The self-assembly of proteins into β-sheet-rich amyloid fibrils has been observed to occur with sigmoidal kinetics, indicating that the system initially is trapped in a metastable state. Here, we use a minimal lattice-based model to explore the ther-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 66 publications
(97 reference statements)
2
8
0
Order By: Relevance
“…Indeed, the behavior of C(T ) displayed in Fig. 3(b) for the aggregation transition studied here, i.e., with C − > C + and ∆C < 0, is also supported by numerical simulations of more detailed aggregation models [44][45][46][47]. Even so, our model-independent kinetic approach can be also applied to study the behavior observed for, e.g., protein folding transitions [48], where one may find that [31] ∆C > 0 and ∆γ < 0.…”
supporting
confidence: 75%
“…Indeed, the behavior of C(T ) displayed in Fig. 3(b) for the aggregation transition studied here, i.e., with C − > C + and ∆C < 0, is also supported by numerical simulations of more detailed aggregation models [44][45][46][47]. Even so, our model-independent kinetic approach can be also applied to study the behavior observed for, e.g., protein folding transitions [48], where one may find that [31] ∆C > 0 and ∆γ < 0.…”
supporting
confidence: 75%
“…Here, many questions are still open, and one often considers explicit heteropolymers/peptides or proteins connected to specific problems. In this context, there has been much recent effort, including full atomistic approaches [115], heteropolymer models [62,116,117,118], tube-like homopolymers [119], extended lattice models [120] and even single-site lattice models [121,122,123], to name only a few. Of course, there is a huge amount of molecular dynamics studies.…”
Section: Aggregation Of Dilute Semiflexible Polymersmentioning
confidence: 99%
“…Flexible polymers were shown to exhibit nucleation hierarchies [124] known from droplet formation. An interesting future question is how this analogy carries over to larger system sizes or to the underlying process itself [123,125,126].…”
Section: Aggregation Of Dilute Semiflexible Polymersmentioning
confidence: 99%
“…The existence of a bad or malfunctioning mechanism by both large and hydrophobic sub-components could indicate a more pronounced global influence of the non-standard residues, but this mechanism is hypothetically possible to occur in other proteins not analyzed yet. The current approach based on two coarse-grained (LS and HP residues) models is suitable in quantitative analyses and when atomic or molecular details can be suppressed or uninterested, but it is rather insufficient for sharper or local measurements, or very specific difference between nonstandard and standard residues, as frequently occur in other applications utilizing coarse-grained models [45][46][47][48]. However, detailed approaches (such as semi-empirical or atomic models) are also limited in many features, since they are very CPU demanding.…”
Section: Non-standard Residues and Molecular Mechanisms In The Targetmentioning
confidence: 99%